Drugs and Constipation in Elderly in Nursing Homes: What Is the Relation? - Gunvor S. Fosnes; Stian Lydersen; Per G. Farup (Gastroenterology Research and Practice)
Introduction. Constipation is a common adverse drug reaction. Objective. Study associations between drugs and constipation in nursing home residents. Design. Cross-sectional study. Material and Methods. Nursing home residents above 60 years of age were included. Demographics, diet, physical activity, activity of daily living, nutritional status, use of drugs, and diseases were recorded. Constipation was defined as functional constipation or constipation-predominant IBS according to the Rome III criteria and/or regular use of laxatives. Drugs were classified according to the Anatomical-Therapeutic-Chemical Classification System (ATC), and anticholinergic effect was noted. Results. In all, 79 men and 188 women with a mean age of 85.4 (SD 7.1) years were included. The prevalence of constipation was 71.5%. Use of drugs in general, including polypharmacy, was not associated with constipation. Reduced activity of daily living (OR = 0.71, 95% CI : 0.60–0.84, P<0.001), other antidepressants (N06AX) (OR 3.08, 95% CI : 1.09–8.68, P=0.03), and benzodiazepine derivatives (N05BA) (OR = 2.80, 95% CI : 1.12–7.04, P=0.03) were significantly associated with constipation; drugs with markedly anticholinergic effect (OR = 3.7, 95% CI : 0.78–17.53, P=0.10), natural opium alkaloid (N02AA) (OR = 5.01, 95% CI : 0.95–25.94, P=0.06), and propionic acid derivatives (M01AE) (OR = 7.00, 95% CI : 0.75–65.08, P=0.09) showed a trend. Conclusion. In elderly with constipation, focus should be on specific groups of drugs and nonpharmacological factors, not on drugs in general.